Exact solutions of the generalized Huxley-Burgers' equations - Tutam, Sevilay Erdogan; Akar, Mutlu (WORLD SCIENTIFIC PUBL CO PTE LTD, 2025)
This study employs the Extended Kudryashov method to address the fractional-order generalized Burgers-Huxley equation, the fractional-order generalized Huxley equation, the fractional-order generalized Burgers equation, and the fractional-order generalized Fisher equation. Through this approach, exact solutions for these equations are derived. Furthermore, we visualize the obtained results in 3D using Maple 2019.2. The outcomes underscore the effectiveness and reliability of the Extended Kudryashov method as a clear and efficient tool for solving the specified equations.
Keywords: The fractional-order generalized nonlinear differential equations; extended Kudryashov method; conformable fractional derivative; TRAVELING-WAVE SOLUTIONS; F-EXPANSION METHOD; KUDRYASHOV METHOD; SOLITONS; MODEL; Physics